In vitro culture of Aloe vera barbadensis mill - Sharifkhani, Ahmad (2012)
Aloe vera is an important medicinal plant species belonging to the family Liliaceae.The gel of Aloe vera makes an excellent treatment for wounds, burns and other skin disorders. Tissue culture technique offers certain advantages over traditional methods of propagation, including making exact copies of the plant;quickly producing mature plants andregeneratingtissue of genetically modified plant. In traditional method of propagation and culture of Aloe verausing adventitious shoots and/or buds the frequency of formation of vegetative shoots is very low. Due to increasing industrial demand for Aloe vera for production of gel, the development of in-vitroregeneration system is necessary to produce unique form and true-to-type plant. The overall goal of this study was to develop a method of in-vitro micropropagation of Aloe vera through shoot regeneration from segment disk explants,follow by rooting and acclimatization. In the experiment on detecting the most suitable explant for in-vitro propagation, leaf tips, ring cross-section discs, adaxial leaf parts, abaxial leaf parts, segment nodal discs and terminal buds of Aloe vera plant were selected for culturing on MS media with and without 6-benzilaminopurine (BAP)and Kinetin (Kin) as plant growth regulator. Among the parts mentioned above, only segment nodal discs regenerated shootson MS medium supplemented with hormones. In determining the most suitable sterilization treatment for reducing explants contamination, without the use of mercuric chloride, explants were treated with different concentrations of sodium hypochlorite(0.525%, 0.787%, 1.050%, 1.312%, and 1.575%).In this method sodium hypochlorite was an alternative to mercuric chloride. The explants were exposed to each concentration for a period of 20 minutes with vigorous and constant shaking. By Kruskal-Walis test (a nonparametric test), 1.050% sodium hypochlorite gave the highest number (91.7%) of alive and sterilized explants with regeneration potential.Based on theseresults, segment nodal discs of Aloe vera were sterilized and cultured on MS media supplemented with different concentrations ofBAP (0, 0.5,1,2,4 and5 mg/l). Data showed that, the number of shoots, increased with the highest mean of shoots per explant on medium supplemented with 4 mg/l BAP and the highest mean percentage of explants producing 100% shootswas obtained on medium with 4 mg/l BAP.The analysis of variance showed significant difference between the treatments. Different concentrations of Kincontrol, 0.5, 1, 2 and 4 mg/l (0, 2.33μM, 4.66μM, 9.30μM and 18.6 μM) were also assessed on shoot multiplication from segment nodal disks.The results reveal that there was no significant difference among different concentrations of Kinetin.Shoot multiplication from segment nodal disks was also studied using different concentrations of Thidiazuron (TDZ) either alone or in combination with Indole-3-butyric acid (IBA). The concentrations of TDZ were 1, 2, 3 and 4 mg/l and five concentrations of IBA were 0, 0.22, 0.57, 1.15 and 2.30 mg/l. Hormone-free MS medium (MSO)was used as control. The highest mean number of shoots proliferated per explant (5.10) was observed on moderate concentration of 2 mg/l TDZ and 1.15 mg/lIBA after eight weeks of culture, which was significantly different with the rest of the treatments. In the study on root induction MS media contain different concentrations of IBA were used. The explants which were previously regenerated using BAP and TDZ - IBA subsequently were cultured on MS media with different concentrations of IBA 0.22, 0.57, 1.15 and 2.30 mg/l. Results showed that the highest mean number of root per explant (5.06) was attained in MS medium supplemented with 1.15 mg/l IBA Highest percentage of root regeneration (100 %) was observed in two concentrations of 1.15 mg/l and 2.30 mg/l IBA followed by 93.33% in 0.57 mg/l IBA. Moreover, highest mean length of roots (14.05 cm) was found in MS medium supplemented with 0.57 mg/l IBA. In the acclimatization study, by applying one-sample Kolmogorove-Smirnove test normality of data was confirmed. On the other hand, the results showed that the plantlets were successfully (96.66 ± 3.33 %) transferred after rooting of microshoots. Using one-sample T-test, no significant difference was revealed between 96.66 % and 100% value of acclimatization of plantlets.